2009
DOI: 10.1007/s11418-009-0331-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychavicol: a potent xanthine oxidase inhibitor obtained from the leaves of betel, Piper betle

Abstract: The screening of Piperaceous plants for xanthine oxidase inhibitory activity revealed that the extract of the leaves of Piper betle possesses potent activity. Activity-guided purification led us to obtain hydroxychavicol as an active principle. Hydroxychavicol is a more potent xanthine oxidase inhibitor than allopurinol, which is clinically used for the treatment of hyperuricemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 11 publications
0
33
0
2
Order By: Relevance
“…They are tastefully eaten by people in India as they taste warm, aromatic and bitter. They are also largely consumed as a mouth freshener and masticator [1], being additionally credited with many biological properties, such as antioxidant [2,3], antimicrobial [4][5][6][7][8], anti-allergic [9], gastroprotective [10], immunomodulator [11], anti-inflammatory [12], chemopreventive [13] and xanthine oxidase inhibitor [14]. As folk medicine, betel leaf is traditionally known to be useful in the treatment of several situations, like boils and abscesses, conjunctivitis, constipation, headache, hysteria, itches, mastitis, mastoiditis, leucorrhoea, otorrhoea, ringworm, swelling of gum, rheumatism, abrasion, bad breath, cuts and injuries [1].…”
Section: Introductionmentioning
confidence: 99%
“…They are tastefully eaten by people in India as they taste warm, aromatic and bitter. They are also largely consumed as a mouth freshener and masticator [1], being additionally credited with many biological properties, such as antioxidant [2,3], antimicrobial [4][5][6][7][8], anti-allergic [9], gastroprotective [10], immunomodulator [11], anti-inflammatory [12], chemopreventive [13] and xanthine oxidase inhibitor [14]. As folk medicine, betel leaf is traditionally known to be useful in the treatment of several situations, like boils and abscesses, conjunctivitis, constipation, headache, hysteria, itches, mastitis, mastoiditis, leucorrhoea, otorrhoea, ringworm, swelling of gum, rheumatism, abrasion, bad breath, cuts and injuries [1].…”
Section: Introductionmentioning
confidence: 99%
“…1). 12) Although the XO inhibitory activity of HC is relatively low compared with febxostat and topiroxostat, its ligand efficiency index 13) value is as high as 0.60, indicating that HC is a good candidate as a seed compound for a modification study. Recently, Honda and Masuda reported that pyrogallol ( Fig.…”
Section: Chemical and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…Based on the literature, A. ceba (Haidari et al, 2008), A. indica and P. betle herbs (Murata et al, 2009) were selected and their potency to inhibit the xanthine oxidase was studied in UV/Visible spectrophotometer at 290 nm. Among the individual and different combination of A. ceba, A. indica and P.betle extracts, the highest inhibition of xanthine oxidase enzyme was noticed in P. betle extracts.…”
Section: In Vitro Spectrophotometric Assaymentioning
confidence: 99%
“…Piperaceous plants are known to contain various catecholic compounds which exhibit antioxidant activity, also piperine obtained from P. betle leaves has shown anti-inflammatory activity (Sabina et al, 2011). A. ceba (Haidari et al, 2008), A. indica and P. betle herbs (Murata et al, 2009) were possess to have xanthine oxidase inhibitory activity. These research backgrounds have prompted us to investigate their xanthine oxidase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%